Pasta containing tartary buckwheat sprouts prevents DNA damage in spontaneously hypertensive rats. (August 2015) - Meschini, Roberta; Filippi, Silvia; Molinari, Romina; Costantini, Lara; Bonafaccia, Giovanni; Merendino, Nicolò
Abstract Recent studies have shown that DNA damage occurs more often in hypertensive patients than non-hypertensive individuals. Here, we analyzed the in vivo effect of pasta containing 30% of tartary buckwheat sprouts (TBSP) on spontaneously hypertensive rats (SHRs) and normotensive Wistar Kyoto rats (WKY) to elucidate if TBSP could have an anti-genotoxic effect in hypertensive animal models. Both SHRs and WKY rats were divided into two groups and fed for six weeks with 5 g of TBSP and durum wheat flour commercial pasta, respectively. Our results showed that a diet rich in TBSP has anti-genotoxic effect. Indeed, SHRs fed with TBSP exhibited a significant decrease in DNA damage (38%) and more efficient DNA repair (84%) compared to SHRs fed with commercial pasta.